2018
DOI: 10.1016/j.foodchem.2018.03.106
|View full text |Cite
|
Sign up to set email alerts
|

Fast and direct analysis of Cr, Cd and Pb in brown sugar by GF AAS

Abstract: A simple and fast analytical method for the determination of Cr, Pb and Cd in brown sugar by GF AAS using slurry sampling was developed and in house validated for the first time. Analytical curves were prepared by external standardization for Cr, and by matrix simulation for Pb and Cd and they were linear. Low limits of quantification for Cr (32.8 ng g), Pb (49.3 ng g) and Cd (4.5 ng g) were found. Repeatability and intermediate precision estimates (<10% and <15%, respectively) and recovery rates (95-103%) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 35 publications
0
12
0
7
Order By: Relevance
“…However, experiments showed that dark brown sugar contained acrylamide levels ranging from 30.17 to 70.17 μg/mL. Brown sugar basically consists of fructose, glucose, and sucrose [44]. We also found that adding dark brown sugar with a high level of acrylamide combined with chitosan or chitooligosaccharide could significantly increase the amount of reducing sugar in the cookie dough (Figure 3a).…”
Section: Reducing Sugar In Brown Sugar Dough and Cookiesmentioning
confidence: 73%
“…However, experiments showed that dark brown sugar contained acrylamide levels ranging from 30.17 to 70.17 μg/mL. Brown sugar basically consists of fructose, glucose, and sucrose [44]. We also found that adding dark brown sugar with a high level of acrylamide combined with chitosan or chitooligosaccharide could significantly increase the amount of reducing sugar in the cookie dough (Figure 3a).…”
Section: Reducing Sugar In Brown Sugar Dough and Cookiesmentioning
confidence: 73%
“…Slurry sampling is a technique of direct sample preparation and known to be capable of minimizing the reported drawbacks of manual and automated sample digestion. This analytical technique is suitable only for graphite furnace AAS [ 38 , 69 ]. There was new application in analysing food samples using AAS such as determination of meat and baby food samples [ 37 ], infant formula [ 40 ], vegetables [ 39 ], fruit juices [ 35 ], fish fillet [ 41 ] and vegetable oils [ 42 ].…”
Section: Mineralsmentioning
confidence: 99%
“…13 Para obter uma suspensão estável e assegurar a precisão e exatidão do método, é necessária a otimização de alguns parâmetros como tamanho de partícula da amostra, razão massa/volume e adição de reagentes estabilizantes, como ácidos ou surfactantes. 13,14 As vantagens da amostragem em suspensão frente aos métodos convencionais de preparo de amostra incluem a simplicidade, rapidez, menor risco de contaminação da amostra e perdas do analito e redução do volume de reagentes tóxicos. [15][16][17] A técnica de espectrometria de absorção atômica em forno de grafite (GF AAS) é uma das mais utilizadas para a determinação de elementos traço em diversos tipos de amostras por apresentar elevada seletividade e sensibilidade.…”
Section: Introductionunclassified
“…Sendo assim, a adição de ácidos e oxidantes às suspensões das amostras ou a utilização de modificadores químicos faz-se necessária muitas vezes para auxiliar na liberação do analito da matriz orgânica e evitar o acúmulo de resíduos no tubo de grafite. 14 A amostragem em suspensão tem sido amplamente utilizada no preparo de diferentes tipos de amostra para a determinação de minerais, especialmente associada às técnicas de espectrometria de absorção atômica. [14][15][16][17][18] Andolfatto 19 utilizou a técnica de amostragem em suspensão para a determinação de Mn, Zn, Fe e Mg em melado de cana por FAAS, sendo que o método otimizado apresentou precisão e exatidão adequadas.…”
Section: Introductionunclassified
See 1 more Smart Citation